Geographic distribution of amino acid mutations in DHFR and DHPS in Plasmodium vivax isolates from Lao PDR, India and Colombia - Saralamba, N; Nakeesathit, S; Mayxay, M; Newton, P; Osorio, L; Kim, J; White, N; Day, N; Dondorp, A; Imwong, M (BioMed Central, 2016)
Background Non-synonymous mutations in dhfr and dhps genes in Plasmodium vivax are associated with sulfadoxine–pyrimethamine (SP) resistance. The present study aimed to assess the prevalence of point mutations in P. vivax dhfr (pvdhfr) and P. vivax dhps (pvdhps) genes in three countries: Lao PDR, India and Colombia. Methods Samples from 203 microscopically diagnosed vivax malaria were collected from the three countries. Five codons at positions 13, 57, 58, 61, and 117 of pvdhfr and two codons at positions 383 and 553 of pvdhps were examined by polymerase chain reaction-restriction fragment length polymorphism methodology. Results The largest number of 58R/117 N double mutations in pvdhfr was observed in Colombia (94.3 %), while the corresponding wild-type amino acids were found at high frequencies in Lao PDR during 2001–2004 (57.8 %). Size polymorphism analysis of the tandem repeats within pvdhfr revealed that 74.3 % of all the isolates carried the type B variant. Eighty-nine per cent of all the isolates examined carried wild-type pvdhps A383 and A553. Conclusions Although SP is not generally used to treat P. vivax infections, mutations in dhfr and dhps that confer antifolate resistance in P. vivax are common. The data strongly suggest that, when used primarily to treat falciparum malaria, SP can exert a substantial selective pressure on P. vivax populations, and this can lead to point mutations in dhfr and dhps. Accurate data on the global geographic distribution of dhfr and dhps genotypes should help to inform anti-malarial drug-use policies.